Beta-lactam-azasugar hybrid as a competitive potent galactosidase inhibitor - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M.; Puranik, Vedavati G. (Tetrahedron Letters, 2006)
A beta-lactam-azasugar hybrid (polyhydroxylated carbacephem) has been designed and synthesized as a potent glycosidase inhibitor. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: beta-Galactosidase; beta-lactam-azasugar; glycosidase inhibitor; hybrid molecules

Convergent approach toward the synthesis of the stereoisomers of C-6 homologues of 1-deoxynojirimycin and their analogues: evaluation as specific glycosidase inhibitors - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M. (Journal of Organic Chemistry, 2006)
A new and stereoselective strategy is developed to synthesize an appropriate template 9 to obtain C-6 homologues of 1-deoxyazasugars such as 1-deoxy-D-galactohomonojirimycin ( 5), 1-deoxy-4-hydroxymethyl-D-glucohomonojirimycin (6), and their enantiomers. The template 9 is also used to obtain neutral nonbasic pseudo-glyconolactam (8), C-4 amino, and methyl analogues of 1-deoxy- homonojirimycin as new analogues of 1- deoxyhomoazasugars. Compound 5 is found to be a potent and specific inhibitor to alpha-galactosidase (K-i = 1.7 mu M). Similarly compounds 6 (K-i = 28 mu M), ent-5 (K-i = 129 mu M), and ent-6 K-i = 12 mu M) exhibited specific inhibition of beta-glucosidase.

Synthesis and evaluation of 1-deoxy-8-epi-castanospermine, 1-deoxy-8-hydroxymethyl castanospermine, and (6S,7S,8R,8aR)-8-amino-octahydroindolizine-6,7-diol - Pandey, Ganesh; Dumbre, Shrinivas G.; Pal, Sujit; Khan, Mohammad Islam; Shabab, A. (Tetrahedron, 2007)
A short, versatile, and enantioselective synthesis of 1-deoxy-8-epi-castanospermine (5), 1-deoxy-8-hydroxymethyl castanospermine (6), and (6S,7S,8R,8aR)-8-amino-octahydroindolizine-6,7-diol (7) is achieved from a common template 12. The key step utilized is PET provoked amine radical cyclization of 11 to 12 in excellent diastereoselectivity. The exocyclic double bond at C-8 of the template is functionalized to obtain 5-7 as exclusive diastereomers. 1-Deoxy-8-epi-castanospermine exhibited inhibition of alpha- and beta-galactosidase and beta-glucosidase. Compounds 6 and 7 were found to be weak inhibitors of beta-glucosidase. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1-deoxy-8-epi-castanospermine; castanospermine; Glycosidase inhibitors

Synthesis of polyhydroxylated conidine alkaloid as a conformationally restricted azasugar - Pal, Sujit; Dumbre, Shrinivas G. (Synlett, 2016)
A conformationally restricted polyhydroxylated 1-azabicyclo[4.2.0]octane core has been synthesized in search for a potent selective glycosidase inhibitor. The key feature of the synthesis involves the high stereoselective photoelectron-transfer-promoted cyclization of the strained alpha-trimethylsilylmethylazetidine moiety to the tethered pi functionality.